A Simplified Frailty Index Predicts Mortality in Older Adults in Beijing - Zhang L; Ji T; Sun F; Li Y; Tang Z; Ma L (Dove Medical Press, 2021)
Li Zhang,1,2,* Tong Ji,1,2,* Fei Sun,2 Yun Li,1 Zhe Tang,1,2 Lina Ma1,2 1Department of Geriatrics, Xuanwu Hospital Capital Medical University, National Clinical Research Center for Geriatric Diseases, Beijing, 100053, People's Republic of China; 2Beijing Geriatric Healthcare Center, Xuanwu Hospital Capital Medical University, Beijing, 100053, People's Republic of China*These authors contributed equally to this workCorrespondence: Lina Ma; Zhe Tang Email malina0883@126.com; tangzhe@sina.comObjective: The comprehensive geriatric assessment (CGA) is an integral tool used to identify vulnerable older adults in need of individualized plans to delay the course of diseases and monitor treatment outcomes. We previously developed and validated a 68-item frailty index (FI) based on the CGA in a large, older, Chinese population. However, substantial time is needed to evaluate the 68 items. Therefore, we aimed to develop and validate a simplified FI for use in Chinese older population.Design: Longitudinal study.Setting and Participants: Data were drawn from the Beijing Longitudinal Study of Aging. The study was conducted in 2004 with 1808 participants evaluated using the CGA and was followed-up for 13 years. Mortality was recorded at 3, 5, 8, 10, and 13 years intervals.Measures: 27-Item, 50-item, and 68-item frailty indices were investigated. A Cox proportional hazards model and area under the curve of the receiver operating characteristic (AUC-ROC) were calculated to compare mortality predictions.Results: The FI was positively correlated with age in males (r = 0.174, P < 0.001) and females (r = 0.270, P < 0.001). The mean baseline FI was 0.225 ± 0.085 (range: 0.04- 0.56) as evaluated by the 27-item FI, 0.181 ± 0.117 (range: 0.02- 0.62) by the 50-item FI, and 0.167 ± 0.101 (range: 0.02- 0.59) by the 68-item FI. Cox regression models showed that mortality was significantly higher in frail people than in non-frail people for all 3 indices (p< 0.001). The AUCs of the 68-item FI, 50-item FI, and 27-item FI for predicting mortality were 0.720, 0.717, and 0.677, respectively (p< 0.001).Conclusion: The 27-item FI is reasonable to expect that the AUC of the indices with the higher items number is inferior to the performance of the indices with higher number of items (FI50 and FI68). But 27-item maybe used as a tool to identify frail older adults and predict mortality in clinical and primary care practices in China.Keywords: frailty index, older adults, comprehensive geriatric assessment, mortality